The Yorkshire Television vitrified wall experiment at East Tullos, City of Aberdeen District (Proceedings of the Society of Antiquaries of Scotland, 1987)
Experimental firing of a full-scale model of a pine-laced wall provoked limited localised vitrification of the hearting. The results may be added to previously garnered evidence to refute the suggestion that vitrification was constructional in intent. The large-scale vitrification of some Scottish sites must have provided a spectacular intimation of destructive power.